2022
DOI: 10.1186/s12939-021-01610-3
|View full text |Cite
|
Sign up to set email alerts
|

The burden of household out-of-pocket healthcare expenditures in Ethiopia: a systematic review and meta-analysis

Abstract: Background In Ethiopia, household Out-Of-Pocket healthcare expenditure accounts for one-third of total healthcare expenditure, is one of the highest in the world, and still creates barriers and difficulties for households to healthcare access and may delay or forgo needed healthcare use. Despite the presence of a few highly dispersed and inconsistent studies, no comprehensive study was conducted. Therefore, in this systematic review and meta-analysis, we aimed at estimating the pooled estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 71 publications
2
16
0
Order By: Relevance
“…Moreover, the curves for the chronically and non-chronically ill both showed a pro-poor distribution, meaning that inequalities are concentrated amongst the less well-off. This confirms that the poor spend a higher share of their income on health compared to the well-off, a finding that is dominant in literature [ 35 , 36 ]. The inequality analysis showed that poor people that also have chronic illness experience even a much higher relative OOP compared to the poor who are not chronically ill.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, the curves for the chronically and non-chronically ill both showed a pro-poor distribution, meaning that inequalities are concentrated amongst the less well-off. This confirms that the poor spend a higher share of their income on health compared to the well-off, a finding that is dominant in literature [ 35 , 36 ]. The inequality analysis showed that poor people that also have chronic illness experience even a much higher relative OOP compared to the poor who are not chronically ill.…”
Section: Discussionsupporting
confidence: 81%
“…With no appropriate financial mechanisms, healthcare seeking in poorly functioning health systems is associated with a risk of catastrophic expenditures [ 50 ]. Borde et al [ 51 ] find that in Ethiopia the average direct out-of-pocket healthcare expenditures were USD 32 per month, the average indirect out-of-pocket healthcare expenditures were USD 15 per month and the average catastrophic healthcare expenditure at 10% of threshold was 40%. Accordingly, consistent with past related studies [ 52 – 55 ], our first hypothesised pathway is that CBHI may have reduced the high out-of-pocket health spending, thereby encouraging utilisation of healthcare services among the PSNP-participating households.…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of OOP health expenditure and CHE headcount was also reported in Kenya, Cameroon, and Nigeria after ten years of implementation of health insurance [ 7 , 8 , 27 ]. Likewise, in Ethiopia, according to a review by Borde et al (2022), the pooled CHE due to OOP expenses during healthcare services was 40.1% at the 10% threshold of non-food expenditure [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of a relatively better level of information in the rest of the world, there is limited evidence on the catastrophic and impoverishing effects of OOP medicine payments in Ethiopia. Previous studies in Ethiopia focused on the total catastrophic and impoverishing implications of OOP health expenditures in general [ 6 , 10 , 18 ]. As such, this study aimed to assess the catastrophic and impoverishing effects of OOP payments on medicines and its trend over time and the contributing factors in the Ethiopian context.…”
Section: Introductionmentioning
confidence: 99%